Patterns of Insect Distribution in Fruit Trees of South Romania and Their Role as Bacterial Vectors - Dana S. Copoiu; Paris Lavin; Corina Itcus; Cristina Purcarea (Diversity)
This study is the first investigation of tree–insect–bacteria interactions in southern Romania, documenting the distribution of 19 insect species across various fruit trees and their insect-associated bacterial diversity. Insect species were identified through DNA barcoding, while bacterial communities in Anthomyia, Botanophila, Drosophila, and Scaptomyza insects were analyzed via 16S rRNA gene sequencing. Insect diversity varied across apple, cherry, plum, peach, and quince trees, with most species showing tree-specific distribution, except for Drosophila melanogaster, which was found on all tree species. Its presence was primarily influenced by fruit development stages rather than temperature changes. Insect bacterial communities comprised 51 genera across four phyla, predominantly Pseudomonadota and Bacillota, that varied by tree species rather than insect species, suggesting the potential role of these flies as bacterial vectors. Several potential pathogenic bacterial genera were identified as biomarkers within insect microbiomes, suggesting their involvement in disease transmission, particularly affecting apple and cherry trees. This study also provides the first report of seven insect species in Romania, being the first microbiome characterization of four dipteran species associated with regional fruit trees.